Dynamics and regulation of glycolysis‐tricarboxylic acid metabolism in the midgut of Spodoptera litura during metamorphosis. Issue 2 (19th December 2015) - Hu, D.; Luo, W.; Fan, L.F.; Liu, F.L.; Gu, J.; Deng, H.M.; Zhang, C.; Huang, L.H.; Feng, Q.L.
Abstract: Significant changes usually take place in the internal metabolism of insects during metamorphosis. The glycolysis‐tricarboxylic acid (glycolysis‐TCA) pathway is important for energy metabolism. To elucidate its dynamics, the mRNA levels of genes involved in this pathway were examined in the midgut of Spodoptera litura during metamorphosis, and the pyruvate content was quantified. The expression patterns of these genes in response to starvation were examined, and the interaction between protein phosphatase 1 (PP1) and phosphofructokinase (PFK) was studied. The results revealed that the expression or activities of most glycolytic enzymes was down‐regulated in prepupae and then recovered in some degree in pupae, and all TCA‐related genes were remarkably suppressed in both the prepupae and pupae. Pyruvate was enriched in the pupal midgut. Taken together, these results suggest that insects decrease both glycolysis and TCA in prepupae to save energy and then up‐regulate glycolysis but down‐regulate TCA in pupae to increase the supply of intermediates for construction of new organs. The expression of all these genes were down‐regulated by starvation, indicating that non‐feeding during metamorphosis may be a regulator of glycolysis‐TCA pathway in the midgut. Importantly, interaction between PP1 and PFK was identified and is suggested to be involved in the regulation of glycolysis.